Disclosure of BMTI: One Size Does Not Fit All? - Rahmawati, Rahmawati; Ab. Rashid, Hafiz Majdi; Annuar, Hairul Azlan; Siraj, Siti Alawiyah (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract. Micro, small, and medium-sized businesses are defined differently indifferent parts of the world because of their disparities in economic development.However, the accounting requirements for those three are the same. This study examines the differences in the disclosure of micro, small, and medium Baitul Maal Wat Tamwil Institutions (BMTI). A total of 206 annual reports of BMTIs in Indonesia were divided based on the size of BMTI and then measured in terms of the extent and quality of disclosure by using 60 items under four dimensions of disclosure: general, financial, social, and Shariah compliance. This study used descriptive statistics analysis as well as one-way analysis of variance (ANOVA). The result showed that the micro BMTIs should be grouped into small-scale enterprises while the medium BMTIs are classified into one broad category. Therefore, regulators should establish size-based reporting standards into two classified entities to foster the growth of BMTIs from micro to small, and medium to big sizes. Abstrak. Usaha mikro, kecil, dan menengah didefinisikan secara berbeda diberbagai belahan dunia karena adanya perbedaan dalam pembangunan ekonomi. Di sisi lain, tidak ada persyaratan akuntansi yang berbeda untuk tiga ukuran. Penelitian ini mengkaji perbedaan pengungkapan Lembaga Baitul Maal Wat Tamwil (BMTI) mikro, kecil, dan menengah. Sebanyak 206 laporan tahunan BMTI di Indonesia dibagi berdasarkan besar kecilnya BMTI, diukur luasnya dan kualitas pengungkapannya dengan menggunakan 60 item yang termasuk dalam empat dimensi: pengungkapan kepatuhan umum, keuangan, sosial dan syariah. Penelitian ini menggunakan analisis statistik deskriptif serta analisis varian satu arah (ANOVA). Hasil penelitian menunjukkan bahwa BMTI mikro dikelompokkan ke dalam usaha skala kecil sedangkan BMTI menengah dikelompokkan ke dalam satu kategori besar. Oleh karena itu. regulator perlu menetapkan standar pelaporan berdasarkan ukuran menjadi dua klasifikas usaha dan untuk mendorong pertumbuhan BMTI dari ukuran mikro ke kecil dan menengah ke besar.